Free Gracilis Muscle Transfers Compared with Nonfree Muscle Flaps for Reanimation of Elbow Flexion: A Meta-Analysis - Scollan, Joseph P.; Newman, Jared M.; Shah, Neil V.; Kuehn, Erika; Koehler, Steven M. (Journal of Hand and Microsurgery, 2019)
Objectives Elbow flexion loss is a debilitating upper extremity injury. Surgical treatment options include nonfree muscle transfers (tendon transfers, nerve transfers, Steindler procedure, Oberlin transfers, and pedicled muscle transfers) or free muscle transfers. We sought to determine if free muscle transfers and nonfree muscle transfers have similar outcomes for elbow flexion reanimation.Materials and Methods A literature search for studies evaluating free and nonfree muscle transfers for elbow flexion reanimation was performed. Included studies reported on transfer failure (strength <M3, unable to flex arm against gravity), strength, range of motion (ROM), or Disabilities of the Arm, Shoulder, and Hand (DASH) score. Pooled odds ratios were used to calculate failure rate, and pooled mean differences were used to calculate differences in strength, ROM, and DASH scores.Results Six studies were included (n = 331 patients). Free muscle patients experienced lower failure rates than nonfree muscle patients. There was no significant difference in ROM. A nonsignificant trend toward better mean strength and DASH scores among free muscle patients was observed.Conclusion Free muscle transfers may be superior to nonfree muscle transfers for elbow flexion reanimation, given their lower failure rates. Well-powered future studies may reveal differences in strength and DASH scores between free and nonfree muscle transfers.
Keywords: elbow flexion reanimation; free muscle transfer; gracilis; meta-analysis; elbow; nerve transfer; brachial plexus; range of motion